EVALUATION THE POTENTIAL OF SUKAMAHI RESERVOIR AT CILIWUNG WATERSHED FOR DKI JAKARTA FLOOD CONTROL - Indah Kusumasari, Rr
Sukamahi Reservoir is a reservoir located in Bogor Regency, West Java. This reservoir is a dry dam has a function as flood control. As flood control, it is necessary to use a building of a spillway to release flood-water. The normal water elevation surface of the sukamahi reservoir is +598 which has a storage volume of 1.48 million m3 and an area of 10.49 Ha. The frequency analysis used is the Gumbel distribution, and the Nakayasu Synthetic Hydrograph. The analytical result effectivity of Sukamahi Reservoir are Q50, Q100, Q1000, and QPMF respectively 32.98%, 37.43%, 29.09% and 1.86% compare of data planning result there is an increase in effectiveness Q100, Q1000, dan QPMF. The type of overflow building is side overflow with Q0.5PMF discharge design that is 244.18 m3 / sec with a total length of 172.2 m. The planned budget for the overflow building is Rp. 124,699,959,037